2016
DOI: 10.1038/cddis.2016.57
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA C2dat1 regulates CaMKIIδ expression to promote neuronal survival through the NF-κB signaling pathway following cerebral ischemia

Abstract: Increasing evidence has demonstrated a significant role of long non-coding RNAs (lncRNAs) in diverse biological processes. However, their functions in cerebral ischemia remain largely unknown. Through an lncRNA array analysis in a rat model of focal cerebral ischemia/reperfusion (I/R), we have identified CAMK2D-associated transcript 1 (C2dat1) as a novel I/R-induced lncRNA that regulated the expression of CaMKIIδ in murine models of focal cerebral ischemia. C2dat1 mRNA was upregulated in a time-dependent manne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
117
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 107 publications
(123 citation statements)
references
References 44 publications
6
117
0
Order By: Relevance
“…For the control cells that were either untransfected (UT) or transfected with an empty vector (vec), OGD/R treatment resulted in progressive neuronal cell death that maximized at about 48 h (30% cell death), in line with previous reports [12]. In contrast, overexpression of CaMKIIδ significantly enhanced cell survival in both N2a (Fig.…”
Section: Camkiiδ and Camkiiγ Promoted Neuronal Survival In Response Tsupporting
confidence: 71%
See 4 more Smart Citations
“…For the control cells that were either untransfected (UT) or transfected with an empty vector (vec), OGD/R treatment resulted in progressive neuronal cell death that maximized at about 48 h (30% cell death), in line with previous reports [12]. In contrast, overexpression of CaMKIIδ significantly enhanced cell survival in both N2a (Fig.…”
Section: Camkiiδ and Camkiiγ Promoted Neuronal Survival In Response Tsupporting
confidence: 71%
“…Our previous study confirmed that C2dat1-induced CaMKIIδ expression promoted neuronal survival through the activation of the NF-κB signaling pathway [12]. To determine if C2dat2 acted through the same signaling mechanisms, both C2dat1 and C2dat2 were depleted in N2a cells and primary neurons followed by OGD/R.…”
Section: Camkiiδ Acted Through the Nf-κb Signaling Pathway To Promotementioning
confidence: 71%
See 3 more Smart Citations